Relevansi Peran Kementerian Koordinator dalam Sistem Presidensial: Studi Komparatif dan Rekomendasi Kebijakan untuk Sistem Pemerintahan Indonesia: The Relevance of the Role of the Coordinating Ministry in the Presidential System: A Comparative Study and Policy Recommendations for the Indonesian Government System - Nasution, Ali Imran; Azaria, Davilla Prawidya; Fauzan, Muhammad; Thoriq, Ahmad Reihan (Perspektif Hukum, 2025)
This paper aims to analyze the relevance of the Coordinating Ministry in carrying out the functions of synchronization and coordination among state ministries in the administration of government in Indonesia, and to compare it with practices in several countries that adopt a Presidential system. The research employs a normative juridical method with statutory, conceptual, and comparative approaches. The findings indicate that the Coordinating Ministry plays a strategic role in maintaining policy coherence among ministries. However, overlapping authority with other ministries that also possess coordinative functions, coupled with the relatively large number of Coordinating Ministers, has the potential to hinder government effectiveness if not managed properly. A comparative study with Presidential countries such as the United States, the Philippines, Brazil, and South Korea suggests that governmental coordination can be carried out more efficiently by a single office or specialized institution. Therefore, this study recommends a reduction in the number of Coordinating Ministers in Indonesia and the strengthening of a single strategic coordinating institution under the President, as well as the possibility for the Vice President to assume a coordinating role when directly mandated by the President.